Laboratory investigations of enteric fever in children: An update - Das, Jagadish C (Journal of Chittagong Medical College Teachers’ Association, 2009)
Key words: enteric fever; investigation; children; blood culture; Widal Test doi: 10.3329/jcmcta.v18i2.3835 Journal of Chittagong Medical College Teachers' Association 2007: 18(2):37-42